Measuring patient activation in the Netherlands: translation and validation of the American short form Patient Activation Measure (PAM13) - Rademakers Jany; Nijman Jessica; van der Hoek Lucas; Heijmans Monique; Rijken Mieke (BMC, 2012)
Abstract Background The American short form Patient Activation Measure (PAM) is a 13-item instrument which assesses patient (or consumer) self-reported knowledge, skills and confidence for self-management of one's health or chronic condition. In this study the PAM was translated into a Dutch version; psychometric properties of the Dutch version were established and the instrument was validated in a panel of chronically ill patients. Methods The translation was done according to WHO guidelines. The PAM 13-Dutch was sent to 4178 members of the Dutch National Panel of people with Chronic illness or Disability (NPCD) in April 2010 (study A) and again to a sub sample of this group (N = 973) in June 2010 (study B). Internal consistency, test-retest reliability and cross-validation with the SBSQ-D (a measure for Health literacy) were computed. The Dutch results were compared to similar Danish and American data. Results The psychometric properties of the PAM 13-Dutch were generally good. The level of internal consistency is good (α = 0.88) and item-rest correlations are moderate to strong. The Dutch mean PAM score (61.3) is comparable to the American (61.9) and lower than the Danish (64.2). The test-retest reliability was moderate. The association with Health literacy was weak to moderate. Conclusions The PAM-13 Dutch is a reliable instrument to measure patient activation. More research is needed into the validity of the Patient Activation Measure, especially with respect to a more comprehensive measure of Health literacy.